Pengidentifikasian pendapatan dan prioritas penggunaan dana desa - Noviyanti Noviyanti; Gading Gamaputra; Yuni Lestari; Dian Arlupi Utami (Publisia: Jurnal Ilmu Administrasi Publik, 2018)
The village fund and village fund allocation policies which have implemented since 2015, require the village apparatus to manage the village budget skillfully in order to optimize the using of it. Bulutengger village in East Java is also expected to be able to synergize the prior programs of village development and community empowerment, while keep following the regulations. This study aims to identify the revenue and the prior allocation which are included in the planning phase based on Minister of Home Affairs Regulation (Permendagri) no. 113 of 2014 on Village Financial Management. This study was conducted by using the qualitative method and descriptive approach. This study finds that the most sources of revenue in Bulutengger Village are village funds, village fund allocation, and village own-source revenue (PADes). The priority of village fund was based on Regent Regulation of Lamongan no. 10 of 2017 on Technical Guidelines for Implementation of Village Fund Financial Management Activities of 2017 Fiscal Year. The priorities are the village development (construction of concrete rebate roads), and community empowerment (integrated service post activities/Posyandu). The using of village fund was also considering the problem statement and the potentials of village in Medium-Term Development Plan of Bulutengger Village (RPJMDesa) 2015-2020. However, most village apparatus is still depended on the head of village to manage the village budget because of the lack of information and knowledge on it.